Anticancer Properties and Clinical Trials of Coumarins: A Review - Shaheen, Hazem M; Nyemb, Jean Noël; Segueni, Narimane; George, Jennifer; Patil, Vishwanath R; Batiha, Gaber El-Saber (Free Radicals and Antioxidants)
Cancer has evolved as one of the most common causes of mortality, worldwide. Though numerous chemotherapeutic treatments are available, their side effects such as cytotoxicity and drug resistance form a big problem during the cancer treatment. Recent studies of anticancer activities conducted on natural products isolated from plants, namely coumarin and related compounds, prove them to be a promising drug candidate in cancer treatments. Efforts made by the scientists to design and develop novel anti-cancer agents using coumarins as lead compounds and study their effectiveness using Structural Activity Relationship is worth appreciating. This review, therefore, focuses on the recent progress in the discovery of coumarin derivatives with potential antitumor activity. It also summarizes their structure- activity relationship, and mechanism of action studies.
Keywords: Cancer; Cytotoxicity; Antitumor activity; Coumarins; Natural produtcs; Structural Activity Relationship